Coupled lattice-expanded Ni and MoO2 array for efficient alkaline hydrogen evolution - Li, Lu (2025)
Transition metal oxides have attracted much attention due to their good electrical conductivity, high chemical stability, and easy electronic structure modulation. However, it is still a great challenge to solve the problems of sluggish reaction kinetics and high overpotential in the alkaline hydrogen evolution reaction (HER) due to their poor intrinsic activity. Herein, a lattice-expanded Ni-decorated MoO2 array (Ni-MoO2-700) catalyst is prepared for the alkaline HER. Unlike most of the reported literature, the decoration of metal heteroatoms may lead to lattice expansion of the carrier catalyst. In contrast, lattice expansion of Ni is also achieved by adjusting the annealing temperature in this work. The Ni-induced lattice-expanding effect can not only modulate the electronic structure of the catalyst but also accelerate electron transfer during the reaction, thus increasing its intrinsic activity for the HER. As a result, Ni-MoO2-700 exhibits significantly enhanced catalytic activity with an overpotential of 74.9 mV at 10 mA cm−2 in 1.0 m KOH, which is far superior to that of most of the reported advanced Ni- and Mo-based materials. This work provides deep intrinsic insight and a great opportunity to design efficient transition metal oxide catalysts for the alkaline HER.